CONCLUSIONS AND RECOMMENDATIONS ON WAYS TO IMPROVE CRITICAL THINKING SKILLS OF HIGH SCHOOL STUDENTS IN CREATIVITY SCHOOLS THROUGH ENGLISH LESSONS - Ismoiljonov Shuxratjon Boymirza o‘g‘li (Research Focus International Scientific Journal, 2024)
This article presents conclusions and recommendations on improving the critical thinking skills of high school students in creativity schools through English lessons. The study emphasizes the importance of critical thinking in the educational process, particularly in fostering intellectual and creative capacities. Various methods and approaches are suggested, including project-based learning, debates, simulations, and critical reading techniques, which can effectively cultivate critical thinking abilities. The article outlines the pedagogical and psychological foundations for enhancing critical thinking and provides a framework for integrating these skills into English lessons. Recommendations focus on developing tailored teaching strategies, teacher training, and incorporating critical thinking elements into assessment systems to encourage students to think analytically and independently.